IoT-Based Smart Education: A Systematic Review of the State of the Art - Hasan, Dler (Apik Cahaya Ilmu, 2025)
The integration of IoT technology into education, known as smart education, has revolutionized traditional learning approaches by establishing interactive and adaptive environments. This article provides a detailed overview of the most recent IoT applications in smart education from 2018 to 2023, highlighting their widespread use and diverse applications. Our primary goals are twofold: first, to investigate the breakthroughs in smart education affected by the integration of IoT applications, based on rigorously analyzed papers; and second, to assess the impact of these improvements on students, educators, and institutional administration. This research includes examining 24 studies (Due to limited articles in this field), identifying 21 IoT applications in smart education, and 26 communication protocols that enable the seamless sharing of information between devices. Despite significant development, obstacles such as network limitations, privacy concerns, and system complexity are acknowledged. The findings emphasize the need for developing a strong infrastructure, overcoming hardware restrictions, and fine-tuning system innovations to achieve seamless incorporation into educational contexts. This study provides useful insights for educators, administrators, and researchers seeking to use the IoT to shape the future of education.